2006
DOI: 10.1001/archotol.132.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of Subcutaneous Amifostine Therapy in Patients With Head and Neck Cancer Treated With Curative Accelerated Concomitant-Boost Radiation Therapy

Abstract: To assess the feasibility and efficacy of subcutaneous amifostine therapy in patients with head and neck cancer treated with curative accelerated radiotherapy (RT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Subcutaneous administration has been tested for the prevention of oral mucositis in head and neck cancer patients, who received radiotherapy or chemoradiotherapy. A total of six articles were reviewed [18,31,[41][42][43][44].…”
Section: Subcutaneous Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Subcutaneous administration has been tested for the prevention of oral mucositis in head and neck cancer patients, who received radiotherapy or chemoradiotherapy. A total of six articles were reviewed [18,31,[41][42][43][44].…”
Section: Subcutaneous Administrationmentioning
confidence: 99%
“…Four articles were reviewed [31,41,43,44]. The rate of oral mucositis was not improved with amifostine in one randomized but neither blinded nor placebo-controlled study [31].…”
Section: Chemoradiotherapy: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of late side effects, grade 3 xerostomia and grade 3 fibrosis occurred in 15% and 0% of the patients, respectively, but their study did not include a control group to compare the efficacy of amifostine. 34 Brizel et al reported the results of a multi-center, randomized phase III study on the efficacy of amifostine that included 315 patients. 35 Assessments were performed weekly before and during RT, and at certain intervals after RT.…”
Section: Discussionmentioning
confidence: 99%
“…44 In a study by Ozsahin et al, despite the fact that amifostine was interrupted due to nausea in 33% of patients and due to hypotension in 18%, it was well tolerated in nearly half of the patients. 34 Law et al noted that grade 1 nausea/ vomiting occurred in 35% of patients after subcutaneous administration. 18 Among the patients in the present study that received intravenous amifostine, 21.9%, 9.7%, and 4.8% had grade 1, 2, and 3 nausea, respectively, 2.4% had syncope, 9.7% had hypotension, and 2.4% had skin rash.…”
Section: Discussionmentioning
confidence: 99%